Elite male and female 800-m runners` display of different pacing strategies during season-best performances - Filipas, L.; Ballati, E. N.; Bonato, M.; La Torre, A.; Piacentini, M. F. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To analyze the pacing profiles of the world's top 800-m annual performances between 2010 and 2016, comparing men's and women's strategies. Methods: A total of 142 performances were characterized for overall race times and 0-to-200-m, 200-to-400-m, 400-to-600-m, and 600-to-800-m split times using available footage from YouTube. Only the best annual performance for each athlete was considered. Overall race and split speed were calculated so that each lap speed could be expressed as a percentage of the mean race speed. Results: The mean speed of the men's 800-m was 7.73 (0.06) m/s, with the 0-to-200-m split faster than the others. After the first split, the speed decreased significantly during the 3 subsequent splits (P < .001). The mean speed of the women's 800-m was 6.77 (0.05) m/s, with a significative variation in speed during the race (P < .001). The first split was faster than the others (P < .001). During the rest of the race, speed was almost constant, and no difference was observed between the other splits. Comparison between men and women revealed that there was an interaction between split and gender (P < .001), showing a different pacing behavior in 800-m competitions. Conclusions: The world's best 800-m performances revealed an important difference in the pacing profile between men and women. Tactics could play a greater role in this difference, but physiological and behavioral characteristics are likely also important.